Cognitive Science and Science Literacy in Physics Education: A Systematic and Bibliometric Mapping of the Research Landscape - Intan Permata Sari; I Made Astra; Hadi Nasbey; Firmanul Catur Wibowo (Universitas Lambung Mangkurat, 2025)
Physics education faces challenges in optimizing the development of high-order thinking skills and science literacy, often being trapped in the transfer of concepts and rote memorization. The integration of cognitive science and science literacy offers a potential solution to address the educational challenges of the 21st century. This research aims to conduct a Systematic Literature Review (SLR) to map the current research landscape (2015-2025) that integrates both domains in physics education. The focus is on identifying dominant trends, utilized methodologies, examined cognitive and science literacy aspects, and formulating pedagogical recommendations. The SLR method adheres to PRISMA guidelines, utilizing article searches in the Scopus database and performing bibliometric analysis with VOSviewer. Key findings indicate an increased focus on computational literacy, the role of visualization in understanding abstract concepts, strategies for developing high-order thinking skills through scientific argumentation, the importance of metacognition and epistemic cognition, as well as the effectiveness of learning approaches such as contextual and cognitive conflict-based in facilitating conceptual change. The VOSviewer analysis visualizes research theme clusters, topic evolution, and collaboration networks, reinforcing qualitative findings. The conclusions of this SLR provide significant implications for physics education practices, emphasizing the need for instructional design based on cognitive principles to achieve comprehensive science literacy, and identifying directions for further research.